A new species of Pseudogastromyzon Nichols (Teleostei: Balitoridae) from Fujian Province, Southeastern China - Chen, I-Shiung; Li, Hsien-En (Zootaxa, 2025)
In this study, a new species of balitorid loach from Fujian Province was collected and described herein, namely Pseudogastromyzon putienensis. The new species can be identified by having dorsal fin iii, 7, anal fin ii, 5, pectoral fin i, 17–18, pelvic fin i, 9, lateral line scales 65–71 and vertebrae counts 38–39. For body and fin colourations, male possess greyish brown with metallic sheen, straight pale bars, and conspicuous rows of large dorsal-fin spots while females with ivory base color and distinct Y-shaped or curved bars, and transparent paired and caudal fins with striped rows. The new species was collected from the Mulan River system and is closely related to Pseudogastromyzon fasciatus; comparisons of the two species are provided herein with comments upon the taxonomy of related congeners in southeastern China.